2001
DOI: 10.1016/s0735-1097(01)01439-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined aerobic and resistance exercise training on vascular function in type 2 diabetes

Abstract: If endothelial dysfunction is an integral component of the pathogenesis of vascular disease, as currently believed, this study supports the value of an exercise program in the management of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
346
8
9

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(400 citation statements)
references
References 39 publications
37
346
8
9
Order By: Relevance
“…Regarding the impact of exercise training on endothelial function in type 2 diabetes and controls, we did not find a significant change in brachial artery FMD across the 8-week exercise training. This observation contrasts with previous studies that report an increase in FMD after training in type 2 diabetes (Colberg et al 2002;Maiorana et al 2001). However, a recent study by Barone Gibbs et al demonstrated no effect of exercise on FMD in type 2 diabetes, despite marked improvements in fitness, body composition, and glycaemic control (Barone Gibbs et al 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the impact of exercise training on endothelial function in type 2 diabetes and controls, we did not find a significant change in brachial artery FMD across the 8-week exercise training. This observation contrasts with previous studies that report an increase in FMD after training in type 2 diabetes (Colberg et al 2002;Maiorana et al 2001). However, a recent study by Barone Gibbs et al demonstrated no effect of exercise on FMD in type 2 diabetes, despite marked improvements in fitness, body composition, and glycaemic control (Barone Gibbs et al 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Although we did not include a non-exercising control group, previous experiments have shown that physical fitness was not altered in subjects that did not perform exercise training (Honkola et al 1997;Maiorana et al 2001). The magnitude of improvement in physical fitness after 8 weeks is in agreement with studies that used an exercise training program of similar duration and intensity (Dunstan et al 1997;Honkola et al 1997;Maiorana et al 2002).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Of the studies otherwise meeting the inclusion criteria, two trials (three articles) were not included since the fitness test was not a maximal aerobic test [35,36,37], three trials (four articles) were excluded because they included a large resistance training component combined with non-continuous aerobic exercise [38,39,40,41] and two articles were excluded since we were unable to differentiate between subjects with and without diabetes [42,43]. Four of the potential articles did not have baseline and post-training VO 2max data available [44,45,46,47] while one trial (two articles) measured post training VO 2max 6 months after the initiation of the 10-week exercise intervention [48,49] and was therefore excluded.…”
Section: Resultsmentioning
confidence: 99%